Reliability prediction for automotive electronics - Piña Monarrez, Manuel Román (2024)
Reliability prediction for electronic products is a fundamental activity for automotive industry for several reasons: 1) understanding if a reliability goal is met, 2) comparing among alternative designs, or 3) evaluating reliability improvements. Reliability prediction is defined by the computation of the failure rates of all electronic components that make up the system/product. In the automotive field there are several guides designed for reliability prediction of electronic components, where the Siemens SN 29500 is well accepted by automotive industry. However, the Siemens SN 29500 standard, as well as other standards, gives the basis for failure rate calculation assuming constant environmental conditions, but not a step-by-step process when products are operating under different environments during their field life. Thus, in this article we present a step-by-step process to fully understand the implementation of the Siemens SN 29500 standard, when environment is not constant, to obtain the failure rate/reliability value of a product following an automotive electronic application